2014
DOI: 10.1088/2041-8205/792/2/l30
|View full text |Cite
|
Sign up to set email alerts
|

Double-Diffusive Mixing in Stellar Interiors in the Presence of Horizontal Gradients

Abstract: We have identified an important source of mixing in stellar radiation zones, that would arise whenever two conditions are satisfied: (1) the presence of an inverse vertical compositional gradient, and (2) the presence of densitycompensating horizontal gradients of temperature (alternatively, entropy) and composition. The former can be caused naturally by any off-center burning process, by atomic diffusion, or by surface accretion. The latter could be caused by rotation, tides, meridional flows, etc. The linear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Several other 3D simulations of thermohaline mixing have been conducted in recent years (Denissenkov & Merryfield 2011;Traxler et al 2011;Brown et al 2013;Medrano et al 2014;Garaud & Brummell 2015). Denissenkov & Merryfield (2011) compared their 3D work to the 2D simulations of Denissenkov (2010) and confirmed the results from the 2D simulations, as well as finding the excitation of gravity waves in their oceanic case but not their RGB case.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Several other 3D simulations of thermohaline mixing have been conducted in recent years (Denissenkov & Merryfield 2011;Traxler et al 2011;Brown et al 2013;Medrano et al 2014;Garaud & Brummell 2015). Denissenkov & Merryfield (2011) compared their 3D work to the 2D simulations of Denissenkov (2010) and confirmed the results from the 2D simulations, as well as finding the excitation of gravity waves in their oceanic case but not their RGB case.…”
Section: Discussionmentioning
confidence: 56%
“…as the Prandtl number decreases), with the thermohaline fingers becoming more like blobs (Traxler et al 2011). Subsequent studies found that thermohaline fingers became blobs over time (Brown et al 2013;Medrano et al 2014;Garaud & Brummell 2015).…”
Section: Discussionmentioning
confidence: 98%
“…This quantity might be considered important because zonal jets grow to sizes comparable with the box, so that the dynamics of the jets could be affected by the periodic boundary conditions. For example, the dynamics of double-diffusive intrusions, in which similar (though not directly analogous) large-scale inclined structures are generated (Simeonov & Stern 2007;Medrano et al 2014), is affected by the degree of inclina-tion of the box relative to the intrusions. In Fig.…”
Section: Evolution In Larger Boxes and Different Aspectmentioning
confidence: 99%
“…Out of the models without braking, on the main sequence the j a = 1 × 10 16 cm 2 s −1 model is the one most similar in terms of surface rotation velocity, and the j a = 7 × 10 16 cm 2 s −1 model is the one most similar in terms of surface abundances. However, many authors (Denissenkov & Pinsonneault 2008a;Vauclair & Théado 2012;Maeder et al 2013) have argued that the strong horizontal turbulence expected in rotating stars (Zahn 1992) should at least curtail thermohaline mixing, if not outright suppress it (also see Medrano et al 2014). If so, it might be more appropriate to exclude thermohaline mixing.…”
Section: Comparison To Observationsmentioning
confidence: 99%